Mössbauer and magnetic study of nanocrystalline strontium hexaferrite prepared by an ionic coordination reaction technique - Araújo, José Humberto de (2013)
Hard-magnetic nanocrystalline strontium hexaferrites SrFe12O19 were synthesized using an ionic coordination reaction technique. In this sample preparation technique the biopolymer chitosan was used as a nanoreactor. The obtained precursor powders were calcined at temperatures in the range 600–900 °C. The samples were analyzed by X-ray diffraction, transmission electron microscopy, Mössbauer spectroscopy and vibrating sample magnetometry. A complementary study of X-ray Rietveld refinement and Mössbauer spectroscopy shown that the hexaferrite phase formation is accompanied by formation of maghemite and hematite as intermediate phases. It was found that hexaferrite is present in the samples calcined at and above 600 °C but it is fully developed at 900 °C. For this sample the average particle size was found to be 41.6 nm. Magnetization measurements yielded squared hysteresis loops with a magnetization ratio () of 0.58 and a coercive field of 6.48 kOe. The overall results indicated that the particles in these samples are in the single domain regime and that the magnetization reversal in these particles is mainly due to coherent rotation